STUDY OF SOCIO-ECONOMIC CONDITIONS WITH THE IMPLEMENTATION OF ORGANIC GOOD AGRICULTURE PRACTICES TOMATO (LYCOPERSICUM ESCULENTUM) CROPS - suswadi, suswadi (Universitas Islam Kadiri, 2024)
The aim of organic farming are to make high-quality and nutritious products, safeguarding environmental health, and sustainable soil ecosystems. SOP-GAP is a right and proper way to raising land, the selection of seeds, fertilizer, pesticides, tools, planting, plant maintenance, fertilizing, irrigation, controlling organisms that annoy plants, and harvesting. The purpose of the study is to identify the relationship between the economic conditions of farmers and the implementation of SOP-inbakes in the village of Senden, Selo district, Boyolali. This â€œArgoayuningtaniâ€ Farmer Group has received a certificate from the office of the Seloliman certification (LESOS) and has received a certificate consistently meeting the requirements of the SOP sni manual and Internal Control System (ICS). documents The analytical methods used were the formulas for values calculations, the spearman ratio correlation, and the testing of hypotheses. Based on the appraisal of the value for polite application, a value of 77.06 percent would be included in a high percentage. From the calculation of a correlation of the rating between the economic condition of the farmers and the implementation of sop-gap, it is known that the value of rho < 0.05, which indicates that there is a correlation between the farmer's socioeconomic conditions and the implementation of SOP-GAP. Then the corelation value varies between 0,440-0,923, which means it has a moderate, strong, and very strong corelation. From tha analysis, there are several unrelated socio-economic factors, including farming experience with pesticides, and land ownership with land cultivation, selection of seeds, fertilizers, presticides, planting, plant maintenance, irrigation, cultivation, and harvesting.